Prenatal alcohol exposure exacerbates acute sensorimotor deficits and impedes long‐term behavioral recovery from the effects of an adult‐onset cerebrovascular ischemic stroke. (24th November 2022) - Bake, Shameena; Hurst, David A.; Miranda, Rajesh C.; Sohrabji, Farida
Abstract: Background: Prenatal alcohol exposure (PAE) is a significant risk factor for developmental disability, although its health consequences across the lifespan are poorly understood. Here, we hypothesized that latent brain and systemic consequences of PAE influence resiliency to adult‐onset neurological disease, specifically, cerebrovascular ischemic stroke. Methods: Pregnant Sprague–Dawley rats were exposed episodically to ethanol during the fetal neurogenic period. Adult (5 months) male and female PAE and control offspring were subjected to endothelin‐1‐induced unilateral middle cerebral artery occlusion. In the acute injury phase outcomes including stroke volume and neurological, endocrine, and gut permeability markers were assessed. Because the effects of stroke in human populations evolve over months to years, we also assessed hippocampal‐ and amygdala‐dependent memory function and social interaction preference up to 6 months following a stroke, in middle‐aged offspring. Results: Prenatal alcohol exposure did not alter infarct volume, but significantly increased neurological deficits in both sexes, and impaired interhemispheric sensorimotor integration in PAE females. The IGF‐1/IGFBP3 ratio, a measure of bioavailable IGF‐1, was significantly reduced, while circulating levels of bacterial lipopolysaccharide, an inflammagen, were significantly increased in PAE males. In PAE females, the circulating IGF‐1/IGFBP3 ratio was significantly increased and estradiol‐17b levels were significantly reduced. The intestinal fatty acid binding protein, a surrogate marker of gut permeability was also significantly increased in PAE females. Longer‐term deficits in hippocampal‐associated memory and social interactions were observed in PAE males, while deficits in amygdala‐dependent memory were observed in PAE females. Conclusions: PAE contributes to adverse effects on brain health and decreased resiliency in response to a common adult‐onset neurovascular disease, cerebrovascular ischemic stroke. Abstract : This study assessed the impact of prenatal alcohol exposure (PAE) on neurobehavioral and endocrine outcomes in 5 to12 month‐old adult rats following ischemic stroke, an acute adult‐onset disease. PAE offspring exhibited greater neurological and endocrine deficits. PAE‐females exhibited decreased sensorimotor integration after stroke compared to non‐PAE controls during the acute phase. PAE males exhibited longer‐term deficits in hippocampal‐associated memory and social interactions, while PAE females showed deficits in hippocampal‐amygdala‐dependent learning. Collectively, PAE reduces resiliency to a common adult‐onset neurological disease.